Physiological and behavioral response of the Asian shore crab, Hemigrapsus sanguineus, to salinity: implications for estuarine distribution and invasion - Hudson, David M. (PeerJ, 2018)
The invasive Asian shore crab, Hemigrapsus sanguineus, is ubiquitous in the rocky intertidal zone of the western North Atlantic. A likely contributor to this colonization is that H. sanguineus is able to handle a wide range of salinities, and is thus more likely to spread through a greater geographic area of estuaries. This study investigated the salinity effects on this animal by observing survival across a range of salinities, the maintenance of hemolymph osmolality under different salinities, and behavioral preference for and avoidance of salinities. H. sanguineus showed high survival across a broad range of salinities, had little change in hemolymph osmolality over a short-term salinity shock, and behaviorally distinguished between salinities when presented with a choice, under both acclimation salinities of 5 PSU or 35 PSU. Such results suggest H. sanguineus has a hardiness for the rapid changes in salinity that happen in the intertidal zone, yet is capable of physically moving to a more optimal salinity. This enhances their competitiveness as an invader, particularly surviving lower salinities that present challenges during high-precipitation events in rocky intertidal areas, and partially explains this species’ dominance in this habitat type.